(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The current research paper explores the relationship between eco-innovation metrics and progress towards UN SDGs, contributing to the discussion on sustainable development. To achieve the research goals, the authors use easily interpretable and statistically significant methods to test the hypotheses, like Pearson correlation coefficients, multiple regression analysis. The methods are considered relevant to demonstrate statistical relationships between UN SDGs and the eco-innovation index, to discuss country performance typologies, and to formulate policy implications for future sustainable development. The results demonstrate that EU countries with higher UN SDG performance tend to have higher eco-innovation scores, moreover, eco-innovation capacities of EU nations are more aligned with the performance on environmental sustainability than on any other aspect of sustainable development. The authors conclude that eco-innovation dimensions operate at diverse levels of influence on the performance of UN SDG 12, while resource efficiency outcomes stand out, being the best predictor, so it should be strongly considered in policy recommendations and strategies.